Household Financial Management in Dealing with The Increase in Food Prices - Isadi, Munir; Magfiroh, Nurul (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
Efforts to fulfill household living needs are highly dependent on income and the ability to manage money obtained from various economic activities. In many cases, economic factors become a major source of disharmony within families. Such disharmony often arises when household income is not balanced with the increasing demands of daily necessities, particularly food expenditure. This study seeks to explore how households, especially homemakers, manage their finances in the face of rising food prices and how they apply accounting practices in everyday financial decision-making. The research employs a qualitative approach through observation, interviews, and documentation, allowing for a deeper understanding of financial behavior at the household level. The findings reveal that homemakers adopt specific strategies to cope with economic pressures, one of which is exercising stricter control over expenditures by avoiding the purchase of non-essential items. Furthermore, their financial management practices reflect the implementation of basic accounting principles, particularly in the areas of budgeting, planning, and decision-making. These aspects serve as practical tools for maintaining financial stability amidst fluctuating prices. Overall, the study highlights the crucial role of homemakers in sustaining household financial resilience and demonstrates that even simple accounting applications can significantly support family well-being in challenging economic conditions.